Konten Social Media Marketing dan Tourist Attractions melalui Minat Berkunjung akan Meningkatkan Keputusan Kunjungan Wisatawan pada UMKM di Kawasan Wisata Jawa Barat - Aggi Panigoro Sarifiyono; Berry Lesmana (Jurnal Maksipreneur, 2023)
Since the Covid-19 pandemic hit the tourism sector, the number of visits has decreased, especially for MSMEs selling at tourist sites. In West Java, the decline in MSMEs selling at tourist sites has decreased as seen from the data from the Central Statistics Agency. This research is how the description and influence of Content Social Media Marketing, Visitor Attractiveness Tourist through visiting interest Visiting Decisions on MSMEs in the West Java Tourism area. The sampling technique uses Cluster Sampling which in sampling as many as 384 respondents, becomes a clump or area, namely Tourist Attractions in West Java. The results of this study indicate that tourist attraction and social media marketing are able to encourage interest and decisions to visit local tourists in the West Java area. As a limitation, this research only focuses on local tourists in several areas in West Java. The dimensions of the tourist attractions variable focus on several attractions in West Java.